"Laudato si'": Reflections on the Ecological Crisis and Climate Change - Sabogal Dunin-Borkowski, Ana (2026)
The ecological crisis we are experiencing today is the result of human actions. We have exploited and polluted the planet beyond measure, exceeding the ecosystem’s capacity to restore itself. In response to this situation, the Church has analyzed the situation in various documents, proposing that human beings be integrated into the conservation and care of the planet. It calls on us to take action to conserve the earth, proposing an integrated management of the Amazon. It thus proposes the term «Integral Ecology» as one that encompasses ecological principles that incorporate the human presence. Any proposal must therefore take human beings into account in order to achieve the conservation of the planet and, specifically, of the Amazon.